Docosahexaenoic Acid Suppresses Silica-Induced Inflammasome Activation and IL-1 Cytokine Release by Interfering With Priming Signal - Wierenga, Kathryn A.; Wee, Josephine; Gilley, Kristen N.; Rajasinghe, Lichchavi D.; Bates, Melissa A.; Gavrilin, Mikhail A.; Holian, Andrij; Pestka, James J. (Frontiers in Immunology, 2019)
Occupational exposure to respirable crystalline silica (cSiO2) has been etiologically linked to human autoimmunity. Intranasal instillation with cSiO2 triggers profuse inflammation in the lung and onset of autoimmunity in lupus-prone mice; however, dietary supplementation with the omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) abrogates these responses. Inflammasome activation, IL-1 cytokine release, and death in alveolar macrophages following cSiO2 exposure are early and critical events that likely contribute to triggering premature autoimmune pathogenesis by this particle. Here we tested the hypothesis that DHA suppresses cSiO2-induced NLRP3 inflammasome activation, IL-1 cytokine release, and cell death in the macrophage. The model used was the murine macrophage RAW 264.7 cell line stably transfected with the inflammasome adapter protein ASC (RAW-ASC). Following priming with LPS, both the canonical activator nigericin and cSiO2 elicited robust inflammasome activation in RAW-ASC cells, as reflected by IL-1β release and caspase-1 activation. These responses were greatly diminished or absent in wild-type RAW cells. In contrast to IL-1β, cSiO2 induced IL-1α release in both RAW-ASC and to a lesser extent in RAW-WT cells after LPS priming. cSiO2-driven effects in RAW-ASC cells were confirmed in bone-marrow derived macrophages. Pre-incubating RAW-ASC cells with 10 and 25 μM DHA for 24 h enriched this fatty acid in the phospholipids by 15- and 25-fold, respectively, at the expense of oleic acid. DHA pre-incubation suppressed inflammasome activation and release of IL-1β and IL-1α by nigericin, cSiO2, and two other crystals – monosodium urate and alum. DHA's suppressive effects were linked to inhibition of LPS-induced Nlrp3, Il1b, and Il1a transcription, potentially through the activation of PPARγ. Finally, nigericin-induced death was inflammasome-dependent, indicative of pyroptosis, and could be inhibited by DHA pretreatment. In contrast, cSiO2-induced death was inflammasome-independent and not inhibited by DHA. Taken together, these findings indicate that DHA suppresses cSiO2-induced inflammasome activation and IL-1 cytokine release in macrophages by acting at the level of priming, but was not protective against cSiO2-induced cell death.